Design and experimental evaluation of a new mechanism for power control of small wind turbines in overspeed wind conditions - Gonzáles Chávez, Salome (2012)
In this work we make the design and testing of a new mechanical element coupled to the vane of a small wind turbine, such that self-regulates and controls the instantaneous power generating wind during overspeed. The rural coast an andean highlands of Peru have high wind potential and on the contrary zero electrical services, in this scenario the provision of electricity by small wind turbines is a strategy solution. One disadvantage of the winds from these areas is its high speed variation, whose adverse effect on the turbine generator is the premature destruction magnet generator winding and turbine blades breakage. Tests were performed on the Wind Tunnel Energy Laboratory- Mechanical Engineering Faculty, Universidad Nacional de Ingeniería-Perú. The results are given in the power curves of the wind turbine prototype. We also demonstrated the reliability of the mechanism when submitting to extreme wind speeds up to the blocking of the turbine generator, as well as the immediate recovery operation when the wind speed returns to nominal turbine generator working conditions.